ChemInform Abstract: Carboxylic Acids as a Traceless Activation Group for Conjugate Additions: A Three‐Step Synthesis of (.+‐.)‐Pregabalin (XXV). Issue 9 (March 2015) - Chu, Lingling; Ohta, Chisa; Zuo, Zhiwei; MacMillan, David W. C.
Abstract A photon‐induced addition is developed which can be applied to a broad spectrum of carboxylic acids including natural and unnatural amino acids.